Standard handbook of machine design (McGraw-Hill, 2004)
The definitive machine design handbook for mechanical engineers, product designers, project engineers, design engineers, and manufacturing engineers covers every aspect of machine construction and operation. The 3rd edition of the Standard Handbook of Machine Design will be redesigned to meet the challenges of a new mechanical engineering age. In addition to adding chapters on structural plastics and adhesives, which are replacing the old nuts bolts and fasteners in design, the author will also update and streamline the remaining chapters.